Effects of Solar Proton Events Associated With X-Ray Flares on Near-Earth Electron and Proton Fluxes Based on ZH-1 Satellite Observations - Wang, Lu; Zhang, Zhenxia; Shen, Xunhui; Li, Xinqiao; Liang, Xiaohua; Zhima, Zeren; Chu, Wei; Guo, Feng; Zhou, Na; Chen, Huaran; Wei, Daihui (Frontiers in Earth Science, 2022)
Solar eruptions can cause violent effects on the space environment. Electromagnetic radiation from solar flares will be the first to arrive on the Earth at the speed of light, followed by solar energetic charged particles. The last to appear will be coronal mass ejections and geomagnetic storms. Based on observations of ZH-1 satellite, we report three strong disturbed space environment events, all of them with solar proton events (SPEs), and analyze the driving mechanisms: 1) On 29 November 2020, an M4.4 flare accompanied with a full halo CME caused a gradual SPE, which was mainly driven by CME shocks. 2) On 28 May 2021, a C9.4 flare brought an impulsive SPE, which was accelerated by the flare. The heliolongitude of this small flare was 63°W, near the footpoint of the magnetic field line leading from the Sun to the Earth. 3) On 28 October 2021, a full-halo CME accompanied with an X1.1 flare brought a gradual SPE. On 2 November 2021, another fast full halo CME accompanied with flare was ejected. The faster CME of November 2 caught up and swept up the slower CME of November 1, and subsequently caused a severe geomagnetic storm (minimum Dst = -101) and a high-energy electron storm on November 4. The observations of the above three space environmental events confirm that the data quality of the high-energy particle package (HEPP) from ZH-1 is highly reliable and accurate and is highly advantageous to monitoring the variation of energetic particles and X-rays in the radiation belt of the Earth during solar activities.